The effect of layer number on mechanical properties and dimensional stability of hybrid kenaf-glass fiber unsaturated polyester composite - Nor Azian, Mohamad (Universiti Malaysia Perlis (UniMAP), 2016)
Hybrid kenaf-glass fiber unsaturated polyester composite was prepared by hand lay-up technique. The kenaf was used in a fiber mat form. The effect of layer number of hybrid kenaf-glass fiber unsaturated polyester composite on mechanical properties and dimensional stability were studied. The effect of layer number of hybrid kenaf-glass fiber unsaturated polyester composite has shown good interfacial adhesion between matrix and fiber reinforced composite thus, increasing the tensile and flexural strength of hybrid kenaf-glass fiber unsaturated polyester composite. Results show that four layer of hybrid kenaf-glass fiber unsaturated polyester composite laminates have the highest tensile strength i.e. 52.665 MPa while highest flexural strength was obtained in two layer of hybrid kenaf-glass fiber unsaturated polyester composite laminate i.e. 92.77 MPa. Three layer of hybrid kenaf-glass fiber unsaturated polyester composite laminate have showed the highest thermal stability at high temperature 452.34˚C with ratio glass fiber to kenaf 2:1. Highest dimensional stability in ethanol solution for 1800 minutes with average of 2 % changes was shown in two layer of hybrid kenaf-glass fiber polyester composite laminate.